Antioxidant Activity and α-Amylase Inhibition of Methanolic Extracts from Selected Bamboo Species: Antioxidant Activity and α-Amylase Inhibition of Bamboo Shoots - Ruiz, Jerome; Pascual, Pet Roey; Alburo, Rosalyn (Journal of Tropical Life Science, 2025)
Bamboo contains bioactive antioxidants, which can be used to scavenge free radicals and prevent degenerative diseases, including diabetes mellitus. The objective of this study is to examine the antioxidative capacity of the bamboo shoot methanolic extracts (Bambusa blumeana, Dendrocalamus asper, and Bambusa vulgaris) as a potential antidiabetic treatment using a spectrophotometric approach. The free radical scavenging and α-amylase inhibitory capacity were measured against known standards. The EC50 was obtained to compare the effectiveness of the three bamboo extracts in reducing free radicals and α-amylase activity by 50%. Among the three extracts, Kuayan tinik (B. blumeana) has the highest total phenolic contents (467.65 ± 6.10 mg GAE/100 g sample), while giant bamboo has the highest total flavonoid contents (875.69 ± 143.47 mg QuE/100 g sample). In addition, the methanolic extract of Kuayan tinik (B. blumeana) has the most optimum antioxidant capacity based on its ability to reduce Fe-radicals (26.93 ± 3.07 mg Fe2+ /100 g sample), scavenge H2O2 (EC50 value = 69.73 ± 0.74 μg/mL), superoxide anion (EC50 value = 62.00 ± 1.27 μg/mL), and DPPH radicals (EC50 value = 57.06 ± 0.44 μg/mL). Kuayan tinik (B. blumeana) also exhibits the highest α-amylase inhibitory activity (EC50 value = 681.10 ± 45.42 μg/mL). Based on the findings, bamboo shoot methanolic extracts show potential for development into dietary supplements. Additionally, the α-amylase inhibition results suggest that bamboo shoot extracts could be further purified and explored for their potential as a diabetic treatment; however, validation through in vivo studies is recommended.